Implementasi Kurikulum MBKM Terhadap Minat dan Hasil Belajar - Saepul Mustakim, Usep (Metakognisi, 2024)
Teaching and learning activities are expected to be carried out well with optimal learning outcomes. The purpose of this study was to find out how effective learning activities are in implementing the "Merdeka Learning Kampus Merdeka" curriculum program or commonly referred to as the MBKM curriculum on student interest and learning outcomes with the hope of increasing learning outcomes. Given the MBKM regulations implementing students to experience learning outside the campus in accordance with their learning interests in the hope of having satisfying learning outcomes and having a positive impact on sparking student competence and motivation in the STKIP Sheikh Manshur environment. The research method used in this study is a quantitative approach where data is obtained by statistical tests that are processed with the help of the SPSS for windows application. The data is accumulated and analyzed using linear regression analysis so that after statistical calculations a value of 75.80% is obtained with an average value of 68.33%, which can be interpreted quite well or it can be said that interest and student learning outcomes are also quite good.